Student Management in the Perspective of Thematic Exegesis: Qur'anic Verses and Hadith on Guidance - Nurul Ulfa Ramadhani; Sarah Fadilah Azzahra; Muhammad Fitriyadi (Pusat Penelitian dan Pengabdian pada Masyarakat (P3M) Sekolah Tinggi Agama Islam As-Sunnah, 2026)
Student management in Islamic educational institutions has tended to focus on administrative and academic matters, while the dimension of spiritual and character development grounded in the Qur'an and Hadith remains insufficiently integrated. This study analyzes the concept of student management through thematic exegesis (mawḍū‘ī), examining Qur'anic verses and hadiths related to student development. The study employs a qualitative library research method, drawing on Qur'anic verses, hadiths from Sahih al-Bukhari, Sahih Muslim, and Sunan Abu Dawud, and authoritative exegetical works, including Tafsir Ibn Kathir, Tafsir al-Maraghi, Tafsir al-Azhar, and Tafsir al-Misbah, as primary data sources. Data were analyzed using Al-Farmawi's thematic exegesis method, with cross-tafsir triangulation applied proportionally according to the complexity of each verse. The findings show that QS. At-Tahrim: 6, QS. Luqman: 13–19, QS. Ali Imran: 159, QS. Al-Kahfi: 66, and QS. An-Nahl: 125, together with its related hadiths, articulates principles of student management encompassing educational responsibility, character formation, compassionate guidance, learning ethics, and methods of mentorship. These principles constitute a revelation-based normative framework for student management in Islamic educational institutions, supporting the holistic development of students across intellectual, moral, and spiritual dimensions.